Varietal selection of high beta-carotene cassava genotypes adapted to dry and humid Caribbean Region of Colombia (2018)
Cassava (Manihot esculenta Crantz) is a four staple crop for human consume worldwide after rice, wheat and corn. Mainly, it is used as energetic source due high carbohydrate content; however, improvement of its nutritional quality can contribute to food security, especially in vulnerable region as Caribe, where several factors have threaten with nutritional balance in children. In Colombia, close to of children are born with a birth weight of less than 2,500 grams, which is one of the main risk factors for the mortality of newborns. In children less than 5 years old, 43,3% has zinc deficiency, 24,3% has A vitamin deficiency and 10,6 has Iron deficiency